2014
DOI: 10.1155/2014/156034
|View full text |Cite
|
Sign up to set email alerts
|

Breast Carcinoma Progression and Tumour Vascular Markers Related to Apoptotic Mechanisms

Abstract: Background. In the last few years, the cancer research had tried to identify and characterize new biochemical and molecular pathways in which the inhibition induces prosurvival mechanisms. Our work describes the expression of two different members of apoptotic regulatory pathway and their relationship with a progression of breast carcinoma. Materials and Methods. We compared expression of genes related to apoptosis (DR6 and Gpm6B) in the blood of patients suffering from stage I of breast cancer in different gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…In addition, GPM6B was profoundly expressed and coexpressed with SMC differentiation markers in embryonic SMCs, indicating that GPM6B might play a role in smooth muscle development. Previous studies have demonstrated that GPM6B is a good vascular marker in breast carcinoma and ovarian carcinoma and have shown that the expression of this protein correlates with the intensity of neovascularization during tumor growth [48][49][50], suggesting its role in tumor angiopoiesis. As SMC differentiation is a critical step in the formation of the vascular system, the essential role of GPM6B in SMC differentiation may implicate this protein as a tumor vascular marker.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GPM6B was profoundly expressed and coexpressed with SMC differentiation markers in embryonic SMCs, indicating that GPM6B might play a role in smooth muscle development. Previous studies have demonstrated that GPM6B is a good vascular marker in breast carcinoma and ovarian carcinoma and have shown that the expression of this protein correlates with the intensity of neovascularization during tumor growth [48][49][50], suggesting its role in tumor angiopoiesis. As SMC differentiation is a critical step in the formation of the vascular system, the essential role of GPM6B in SMC differentiation may implicate this protein as a tumor vascular marker.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that high levels of TNFSF9 in TNBC (Figure 4 and Supplementary Figure 3) might inhibit CD8+TILs to reduce cytotoxicity, leading to enhanced aggressiveness of TNBC. TNFRSF21 (DR6) level is known to be increased in a grade-dependent manner in BC [69], although the functional role of TNFRSF21 in TNBC is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that GPM6B plays an important role in myelination, neuronal differentiation, and osteoblast differentiation. Some oncology research data have also indicated that GPM6B can be used as a biomarker for gynecological malignancies and breast carcinoma [ 16 , 18 ]. Studies by Fjorback et al [ 14 ] confirmed that the expression of Gpm6B significantly decreased serotonin uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Oncological research on GPM6B has gradually attracted attention in recent years. In breast cancer, GPM6B can be used as a marker of tumor angiogenesis [ 16 ] In a study of the gynecological malignancies, namely, endometrial cancer, uterine cancer, and ovarian cancer, the expression level of Gpm6B was markedly elevated in patient tumor tissues and higher in the peripheral blood of patients than that of healthy controls [ 17 ]. Acting as a protooncogene, GPM6B also upregulates expression in a variety of types of human B lymphocytic leukemia [ 18 ].…”
Section: Introductionmentioning
confidence: 99%